Drusen in the macula and parapapillary region - Jonas, Jost B.; Panda-Jonas, Songhomitra; Jonas, Rahul A. (Graefe's archive for clinical and experimental ophthalmology, 2024)
Purpose: To examine histological characteristics and differences between drusen beneath the retinal pigment epithelium (small hard drusen) located in the macula and located in the parapapillary region. Methods: We histomorphometrically examined human eyes enucleated due to uveal melanomas or secondary angle-closure glaucoma. Results: The study included 106 eyes (age, 62.6 ± 15.2 years) with macular drusen (n = 7 globes) or parapapillary drusen (n = 29 eyes) and 70 eyes without drusen. In all drusen, periodic-acid-Schiff-positive material was located between the RPE basal membrane and the inner collagenous layer of Bruch’s membrane (BM). Macular drusen as compared with parapapillary drusen had lower height (15.2 ± 10.1 µm versus 34.3 ± 19.8 µm; P = 0.003), while both groups did not differ significantly in basal drusen width (74.0 ± 36.3 µm versus 108.7 ± 101.0 µm; P = 0.95). Eyes with macular drusen and eyes without drusen did not differ significantly in BM thickness (2.74 ± 0.44 µm versus 2.55 ± 0.88 µm; P = 0.57) or in RPE cell density (35.4 ± 10.4 cells/480 µm versus 32.8 ± 7.5 cells/480 µm; P = 0.53), neither in the drusen region nor in the drusen vicinity, while BM thickness (4.60 ± 1.490 µm; P < 0.001) and RPE cell density (56.9 ± 26.8 cells/480 µm; P = 0.005) were higher at the parapapillary drusen. Eyes with macular drusen, eyes with parapapillary drusen, and eyes without drusen did not differ significantly in choriocapillaris density (all P > 0.10) and thickness (all P > 0.35). Limitations of the study, among others, were a small number and size of drusen examined, diseases leading to enucleation, lack of serial sections, limited resolution of light microscopy, and enucleation-related and histological preparation-associated artefacts. Conclusions: The findings of this study, also taking into account its methodological limitations, suggest that macular drusen and parapapillary drusen shared the morphological feature of periodic-acid-Schiff-positive material between the RPE basal membrane and BM and that they did not vary significantly in choriocapillaris thickness and density. RPE cell density and BM thickness were higher in parapapillary drusen than in macular drusen.
Online veröffentlicht: 13. März 2024
Gesehen am 25.07.2024